1989
DOI: 10.1063/1.344335
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanisms of strain release in molecular-beam-epitaxy-grown InxGa1−xAs/GaAs single heterostructures

Abstract: Electroreflectance study of effects of indium segregation in molecular-beam-epitaxy-grown InGaAs/GaAsTunneling microscopy and spectroscopy on cross sections of molecularbeamepitaxygrown (Al)GaAs multilayers J. Vac. Sci. Technol. B 9, 779 (1991); 10.1116/1.585510 dc and ac transport in molecularbeamepitaxygrown metal/ZnSe/GaAs heterojunction structures Summary Abstract: Molecularbeam epitaxial growth of (Al,Ga) As/GaAs heterostructures with interruption at interfaces InxGa l _ xAs/GaAs single heterostructures h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(39 citation statements)
references
References 28 publications
2
34
0
3
Order By: Relevance
“…On the other hand, it has also been shown that during epitaxial growth, the non-equilibrium kinetics of dislocation formation can lead to e / d À1=2 (or U / d À1 ). 35 In contrast, much less is known about the value of L that determines the thickness dependence of the domain wall energy. Since the energy cost of the walls is proportional to the spontaneous strain in the domains, a thickness dependence of the residual strain must also result in a thickness dependence of the domain wall energy.…”
mentioning
confidence: 99%
“…On the other hand, it has also been shown that during epitaxial growth, the non-equilibrium kinetics of dislocation formation can lead to e / d À1=2 (or U / d À1 ). 35 In contrast, much less is known about the value of L that determines the thickness dependence of the domain wall energy. Since the energy cost of the walls is proportional to the spontaneous strain in the domains, a thickness dependence of the residual strain must also result in a thickness dependence of the domain wall energy.…”
mentioning
confidence: 99%
“…(8) is very close to the equation describing the strain relief in a single layer heterostructure. As was shown in [11], the strain relief of epitaxial layer of In Ga As grown on (001) GaAs substrate is governed by the equation…”
Section: Discussionmentioning
confidence: 99%
“…Such a relation between strains and thicknesses was explained in the framework of a "geometrical approach" taking into account the character of the spatial distribution of misfit dislocations in the region between the substrate and the growing epitaxial layer. By contrary, in [11] there was established that the residual compressive strain varies in an inverse proportion to the root square of layer thickness. It means that there is an energetic limit for an elastic strained thin film, which governs the strain relief in single layer hetero structures.…”
Section: Introductionmentioning
confidence: 98%
“…Обращает на себя внимание то,что по своей форме выражение (8) близко к выражению, полученному в [12] для описания структурной релак-сации в однослойных гетерофазных структурах, выра-щенных на подложках (001) GaAs на основе тройных растворов In x Ga 1−x As при x = 0.1−0.4. Согласно [12], процесс структурной релаксации в таких однослойных гетероструктурах следует закону…”
Section: обсуждение результатовunclassified
“…Эта зависимость была объяснена особенностями поведения дислокаций несоответствия в приграничном (в области подложки) слое на основе геометрического подхода [11], базирующегося на суще-ствовании предельной плотности дислокаций несоответ-ствия, превышение которой приводит к пластической деформации. Авторами [12] по результатам собственных исследований, а также на основе экспериментальных данных, приведенных в [13][14][15], было установлено, что связь между остаточными упругими деформациями и толщинами слоев в однослойных гетероструктурах под-чиняется обратной квадратно-корневой зависимости, что свидетельствует о существовании некоторого энергети-ческого предела, выше которого дальнейшее упругое сжатие решетки эпитаксиального слоя невозможно. Для обоих подходов были найдены значения феноменоло-гических постоянных, позволяющих численно выразить остаточную упругую деформацию в зависимости от толщины эпитаксиального слоя.…”
Section: Introductionunclassified